A method for selective hydrogenation of vinyl acetylene
Patent Information
- Application Number
- CN202211224591.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-09
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-10-09
AI Technical Summary
[0006]本发明所要解决的技术问题是现有技术中碳四馏分中乙烯基乙炔转化率低、丁二烯损失率高、催化剂稳定性差的技术问题,提供一种新的乙烯基乙炔选择加氢的方法
[0031]采用本发明制备的硫化型双金属镍银催化剂进行乙烯基乙炔加氢处理,催化剂表现出更好的乙烯基乙炔加氢选择性,不仅进料中丁二烯不损失,而且乙烯基乙炔中大部分在反应过程中加氢为丁二烯,少量加氢为单烯烃,可实现最大化转化乙烯基乙炔,同时丁二烯的损失率降至最低,而且催化剂的稳定性可得到明显改善。
Smart Images

Figure BDA0003879064150000081 
Figure BDA0003879064150000082 
Figure BDA0003879064150000091
Abstract
Description
Technical Field
[0001] This invention relates to a method for selective hydrogenation of vinylacetylene, particularly a method for selective hydrogenation of vinylacetylene in C4 fractions. Background Technology
[0002] The cracked C4 fraction, a byproduct of ethylene plants, typically contains 40-60% (wt) butadiene and 1.0-2.0% (wt) alkynes. Butadiene is an important monomer in the synthetic rubber industry, and the presence of alkynes poses numerous difficulties for its separation, especially vinylacetylene, which readily polymerizes and clogs equipment. High concentrations of vinylacetylene can also easily cause explosions and accidents. Currently, industrially, extractive distillation methods are commonly used to extract butadiene from the cracked C4 fraction, such as the acetonitrile method, the N-methylpyrrolidone method, and the dimethylformamide (DMF) method. As the cracking depth of ethylene plants increases, the alkyne content in cracked C4 gradually increases, affecting separation energy consumption. Meanwhile, the purity of polymer-grade butadiene needs to be greater than 99.7%, and the alkyne content needs to be less than 25 ppm. Therefore, the preferred industrial option is to add a selective hydrogenation reactor before butadiene separation to selectively hydrogenate alkynes such as vinylacetylene in the butadiene-rich fraction. This not only reduces the energy consumption of subsequent separation but also increases the product yield of butadiene, thereby improving the purity of polymer-grade butadiene.
[0003] Chinese patent CN200810239462.3 discloses a selective hydrogenation method for highly unsaturated hydrocarbons in C4 fractions. Using the alkyne-rich residue obtained after butadiene extraction as raw material, a fixed-bed reactor is employed. In the presence of a catalyst, butadiene is selectively hydrogenated to obtain butadiene, and the reaction product is then returned to the extraction unit. This achieves the goal of increasing butadiene production. The hydrogenation process conditions are: reaction temperature 30–90℃, reaction pressure 1.0–4.0 MPa, and liquid hourly space velocity 7–20 h⁻¹. -1 The catalyst is palladium / alumina with a specific surface area of 50–150 m². 2 / g, with a specific pore volume of 0.25–1.0 ml / g. This method uses a precious metal catalyst, which results in high costs and affects the overall efficiency of the equipment.
[0004] Chinese patent CN03159237.6 discloses a two-stage hydrogenation utilization method for alkyne-rich products generated by a butadiene extraction device. The first stage reactor is an adiabatic bubbling bed reactor, using a two-component or multi-component catalyst containing a Group VIII metal. The second stage reactor is also an adiabatic bubbling bed reactor, using a catalyst containing a Group VIII metal as the active component. In this method, both alkynes and 1,3-butadiene in the exhaust gas are hydrogenated to 1-butene, without selectively hydrogenating vinylacetylene to butadiene.
[0005] As is well known, in the C4 fraction of high-concentration vinylacetylene and butadiene, the hydrogenation catalyst exhibits the highest activity for vinylacetylene, and it undergoes hydrogenation first. Only after vinylacetylene has been almost completely hydrogenated does butadiene participate in the hydrogenation reaction. If the catalyst has poor selectivity, causing butadiene to also be hydrogenated, it will result in a significant loss of butadiene. Summary of the Invention
[0006] The technical problem to be solved by this invention is the low conversion rate of vinylacetylene, high butadiene loss rate, and poor catalyst stability in C4 fractions of existing technologies. This invention provides a novel method for the selective hydrogenation of vinylacetylene. This method has the advantages of high vinylacetylene removal rate, low butadiene loss rate, and good stability.
[0007] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:
[0008] A method for selective hydrogenation of vinylacetylene includes the step of contacting vinylacetylene with a catalyst under effective reaction conditions to enhance the production of butadiene, said catalyst comprising, by weight percentage:
[0009] (a) 5.0 to 40.0% metallic nickel or its oxide, based on the content of nickel element therein;
[0010] (b) 1.0 to 20.0% metallic silver or its oxide, based on the amount of silver in it;
[0011] (c) 0.1% to 3.0% of at least one element selected from IA of the periodic table or its oxide, based on the content of the IA element therein;
[0012] (d) 1.0 to 10.0% sulfur or its compounds, based on the sulfur content therein;
[0013] (e) The balance of aluminum oxide.
[0014] In the above technical solution, the effective reaction conditions include: hydrogen pressure 1.0-2.0 MPa, reaction temperature 30-80℃, and fresh oil space velocity 1.0-2.0 h⁻¹. -1 The hydrogen / oil volume ratio is 50:1-200:1.
[0015] In the above technical solution, the specific surface area of the catalyst is 50-200 m². 2 / g, pore volume of 0.4-0.6cm 3 / g.
[0016] In the above technical solution, the catalyst, by weight percentage, comprises 10.0-30.0% nickel or its oxide; 3.0-15.0% silver or its oxide; 0.2-2.0% at least one element selected from IA of the periodic table or its oxide; and 2.0-8.0% sulfur or its compound.
[0017] In the above technical solution, the element selected from IA of the periodic table is preferably at least one of lithium or potassium.
[0018] In the above technical solution, the sulfur or its compound is preferably at least one of hydrogen sulfide, dimethyl disulfide, and carbon disulfide.
[0019] In the above technical solution, the method for preparing the catalyst is as follows:
[0020] (1) The pseudoboehmite, guar gum powder, adhesive solvent and water are mixed and shaped, and then dried and calcined in air to obtain the modified alumina carrier;
[0021] (2) A solution composed of nickel precursor, silver precursor, lithium and / or potassium precursor is brought into contact with the modified alumina support described above. The preferred contact method is impregnation. After contact, the support is dried and calcined in air to obtain an oxidized catalyst. The above steps can be repeated to obtain the desired nickel, silver and other metal content.
[0022] (3) Reduced under certain conditions, and then sulfided in a hydrogen atmosphere containing sulfur or its compounds to obtain the finished catalyst.
[0023] In the above technical solution, the adhesive solvent is preferably at least one of nitric acid, acetic acid, and polyvinyl alcohol.
[0024] In the above technical solution, the drying temperature for preparing the modified alumina carrier in step (1) is preferably 100-150℃, and the drying time is preferably 10-15h; the calcination temperature is preferably 1000-1200℃, and the calcination time is preferably 4-8h.
[0025] In the above technical solution, the nickel precursor in step (2) is preferably nickel nitrate; the silver precursor is preferably silver nitrate; the lithium precursor is preferably lithium nitrate; and the potassium precursor is preferably potassium nitrate.
[0026] In the above technical solution, the drying temperature for preparing the oxidative catalyst in step (2) is preferably 100-150℃, and the drying time is preferably 4-10h; the calcination temperature is preferably 400-600℃, and the calcination time is preferably 4-8h.
[0027] In the above technical solution, the reduction conditions in step (3) are: temperature 400-500℃, pressure 0.1-1.0MPa, and hydrogen space velocity 500-1500h.-1 The restoration time is 10-30 hours.
[0028] In the above technical solution, the vulcanization conditions in step (3) are: temperature 300-400℃, pressure 0.1-1.0MPa, and gas space velocity 400-800h. -1 Vulcanization time: 2-10 hours.
[0029] As is well known, the hydrogenation reaction of vinylacetylene is a typical series reaction, with butadiene and butene as intermediate products. Excessive hydrogenation produces butane. However, in the process of recovering butadiene from C4 fractions, the added value of butane and butene is far lower than that of butadiene. Furthermore, the presence of trace amounts of vinylacetylene is detrimental to subsequent butadiene separation and purification processes. Therefore, maximizing the conversion of vinylacetylene while minimizing butadiene loss is crucial for butadiene recovery from butadiene-rich C4 fractions. During the hydrogenation of vinylacetylene, the activation energy for hydrogenating vinylacetylene to butadiene is lower than that for hydrogenating butadiene to butene and butane. This provides an important theoretical basis for the selective hydrogenation of vinylacetylene from a reaction kinetic perspective.
[0030] In the selective hydrogenation of alkynes, single-metal catalysts readily form strong complexes with alkyne bonds, causing them to gradually dissolve into the reaction medium along with the adsorbed hydrocarbons, resulting in permanent catalyst deactivation. Simultaneously, strong complex adsorption can lead to over-hydrogenation, reducing reaction selectivity. The inventors have discovered that adding a second or more metals to the catalyst, along with sulfidation treatment, weakens the strong adsorption of alkynes and active metals due to the interaction between the metals after alloy formation and the alteration of the electronic properties of the active metals by the introduction of sulfur. This prevents the loss of active components from the catalyst and promotes the desorption of butadiene, thereby improving hydrogenation selectivity. Furthermore, the increased dispersion of active components on the support further enhances the catalyst's stability.
[0031] When the sulfide-type bimetallic nickel-silver catalyst prepared in this invention is used for the hydrogenation of vinyl acetylene, the catalyst exhibits better selectivity for vinyl acetylene hydrogenation. Not only is there no loss of butadiene in the feed, but most of the vinyl acetylene is hydrogenated to butadiene during the reaction, and a small amount is hydrogenated to mono-olefins. This maximizes the conversion of vinyl acetylene, minimizes the loss rate of butadiene, and significantly improves the stability of the catalyst.
[0032] The catalyst of this invention, when used for the selective hydrogenation of vinyl acetylene in the C4 fraction of butadiene extraction, can maximize the conversion of vinyl acetylene while minimizing the loss rate of butadiene, and exhibits good low-temperature activity, selectivity and stability.
[0033] Using the catalyst of this invention, a C4 fraction containing 5.0 wt% vinylacetylene and 30 wt% butadiene was used as feedstock. The reaction was carried out at a temperature of 40°C, a pressure of 1.5 MPa, and a fresh oil space velocity of 1.5 h⁻¹. -1 Under the condition of a hydrogen / oil volume ratio of 100:1, the hydrogenation conversion rate of vinylacetylene can reach up to 100%, and butadiene can be obtained with no loss or even growth. The catalyst has good stability and has achieved good technical results.
[0034] The present invention will be further illustrated below by way of examples. However, these examples do not in any way limit the scope of the present invention. Detailed Implementation
[0035]
Example 1
[0036] Weigh 150 g of boehmite and 3.0 g of guar gum powder, then add 145 ml of an aqueous solution containing 25 g of polyvinyl alcohol solution (mass concentration of 5%), 2.0 g of nitric acid and 1.5 g of acetic acid, and extrude it into 2.0 mm clover strips. After drying the wet strips at 110 °C for 12 hours, they are calcined at 1100 °C for 4 hours to obtain alumina carrier Z1.
[0037] Weigh 100g of support and prepare the catalyst according to the ratio of 20% Ni + 5% Ag + 1.5% K + 5% S (based on catalyst weight). First, weigh out nickel nitrate, silver nitrate, and potassium nitrate, and dissolve them in water to make 85ml of solution. Impregnate the support in the solution in equal volumes, dry at 110℃ for 6 hours, calcine at 450℃ for 7 hours, and then calcine at 450℃, 0.1MPa, and H2 space velocity of 1000h⁻¹. -1 The sample was reduced for 15 hours under the following conditions, and then further reduced in an H2 atmosphere containing 2 mol% sulfur (hydrogen sulfide) at 320°C, 0.1 MPa, and a gas hourly space velocity of 500 h⁻¹. -1 Catalyst C1 was obtained by sulfidation treatment for 5 hours under the specified conditions. The composition of the catalyst is shown in Table 1.
[0038]
Example 2
[0039] Weigh 150 g of boehmite and 3.0 g of guar gum powder, then add 145 ml of an aqueous solution containing 25 g of polyvinyl alcohol solution (mass concentration of 5%) and 2.0 g of nitric acid. Extrude the mixture into 2.0 mm clover strips. After drying the wet strips at 110 °C for 10 hours, calcine them at 1000 °C for 5 hours to obtain alumina carrier Z2.
[0040] Weigh 100g of support and prepare the catalyst according to the ratio of 30% Ni + 10% Ag + 2% Li + 6% S (based on catalyst weight). First, weigh out nickel nitrate, silver nitrate, and lithium nitrate, and dissolve them in water to make 88ml of solution. Impregnate the support in the solution in equal volumes, dry at 120℃ for 4 hours, calcine at 500℃ for 4 hours, and then calcine at 500℃, 0.6MPa, and H2 space velocity of 500h⁻¹. -1 The sample was reduced for 30 hours under the specified conditions, and then further reduced in an H2 atmosphere containing 2 mol% sulfur (dimethyl disulfide) at 300 °C, 0.6 MPa, and a gas hourly space velocity of 600 h⁻¹. -1 Catalyst C2 was obtained by sulfidation treatment for 8 hours under the specified conditions. The composition of the catalyst is shown in Table 1.
[0041]
Example 3
[0042] Weigh 150 g of boehmite and 3.0 g of guar gum powder, then add 145 ml of an aqueous solution containing 25 g of polyvinyl alcohol solution (mass concentration of 5%) and 1.5 g of acetic acid. Extrude the mixture into 2.0 mm clover strips. After drying the wet strips at 140 °C for 13 hours, calcine them at 1150 °C for 6 hours to obtain alumina carrier Z3.
[0043] Weigh 100g of support and prepare the catalyst by weight in the following ratio: 10% Ni + 15% Ag + 1.0% Li + 1.0% K + 4% S. First, weigh out nickel nitrate, silver nitrate, lithium nitrate, and potassium nitrate, and dissolve them in water to a volume of 75ml. Impregnate the support in the solution in equal amounts, dry at 130℃ for 7 hours, calcine at 550℃ for 5 hours, and then perform a final calcination at 480℃, 0.7 MPa, and H₂ space velocity of 1500 h⁻¹. -1 The sample was reduced for 10 hours under the following conditions, and then subjected to a H2 atmosphere containing 2 mol% sulfur (carbon disulfide) at 350°C, 0.7 MPa, and a gas hourly space velocity of 400 h⁻¹. -1 Under the specified conditions, the catalyst C3 was obtained by sulfidation treatment for 4 hours. The composition of the catalyst is shown in Table 1.
[0044]
Example 4
[0045] Using Z1 as the support, 100g of the support was weighed. Based on the catalyst weight, a catalyst was prepared according to the ratio of 5% Ni + 20% Ag + 2% K + 8% S. Nickel nitrate, silver nitrate, and potassium nitrate were weighed and dissolved in water to a final volume of 85ml. The support was then impregnated in the solution in equal amounts, dried at 150℃ for 5 hours, calcined at 400℃ for 8 hours, and then subjected to a reaction at 490℃, 0.4 MPa, and an H2 space velocity of 1200 h⁻¹. -1 The sample was reduced for 20 hours under the following conditions, and then further reduced in an H2 atmosphere containing 2 mol% sulfur (dimethyl disulfide) at 400°C, 0.4 MPa, and a gas hourly space velocity of 700 h⁻¹. -1 Catalyst C4 was obtained by sulfidation treatment for 6 hours under the specified conditions. The composition of the catalyst is shown in Table 1.
[0046]
Example 5
[0047] Using Z2 as a support, 100g of support was weighed. Based on the catalyst weight, a catalyst was prepared according to the ratio of 40% Ni + 1.0% Ag + 2.0% Li + 10% S. Nickel nitrate, silver nitrate, and lithium nitrate were weighed and dissolved in water to a final volume of 75ml. The support was then impregnated in the solution in equal amounts, dried at 140℃ for 9 hours, calcined at 500℃ for 6 hours, and then subjected to a reaction at 420℃, 0.3 MPa, and an H2 space velocity of 800 h⁻¹. -1 The sample was reduced for 25 hours under the specified conditions, and then further reduced in an H2 atmosphere containing 2 mol% sulfur (carbon disulfide) at 370°C, 0.3 MPa, and a gas hourly space velocity of 800 h⁻¹. -1 Under the specified conditions, the catalyst C5 was obtained by sulfidation treatment for 10 hours. The catalyst composition is shown in Table 2.
[0048]
Example 6
[0049] Using Z3 as the support, 100g of the support was weighed. Based on the catalyst weight, a catalyst was prepared according to the ratio of 15% Ni + 10% Ag + 0.1% Li + 6% S. Nickel nitrate, silver nitrate, and lithium nitrate were weighed and dissolved in water to a final volume of 75ml. The support was then impregnated in the solution in equal amounts, dried at 100℃ for 8 hours, calcined at 480℃ for 5 hours, and then subjected to a reaction at 400℃, 1.0 MPa, and an H2 space velocity of 700 h⁻¹. -1 The sample was reduced for 28 hours under the specified conditions, and then further reduced in an H2 atmosphere containing 2 mol% sulfur (dimethyl disulfide) at 380°C, 1.0 MPa, and a gas hourly space velocity of 550 h⁻¹. -1 Catalyst C6 was obtained by sulfidation treatment for 7 hours under the specified conditions. The composition of the catalyst is shown in Table 2.
[0050]
Example 7
[0051] 150 g of boehmite and 3.0 g of guar gum powder were weighed, and then 145 mL of an aqueous solution containing 2.0 g of nitric acid was added. The mixture was extruded into 2.0 mm clover-shaped pieces. The wet strips were dried at 110 °C for 13 hours and then calcined at 1050 °C for 6 hours to obtain alumina support Z4. 100 g of the support was weighed, and a catalyst was prepared by weighting the catalyst according to the ratio of 20% Ni + 10% Ag + 0.5% K + 1% S. Nickel nitrate, silver nitrate, and potassium nitrate were weighed and dissolved in water to a volume of 86 mL. The support was impregnated in the solution in equal amounts, dried at 110 °C for 10 hours, calcined at 450 °C for 5 hours, and then subjected to a reaction at 470 °C, 0.9 MPa, and an H2 space velocity of 900 h⁻¹. -1 The sample was reduced for 13 hours under the following conditions, and then further reduced in an H2 atmosphere containing 2 mol% sulfur (hydrogen sulfide) at 310 °C, 0.9 MPa, and a gas hourly space velocity of 650 h⁻¹. -1 Under the specified conditions, the catalyst C7 was obtained by sulfidation treatment for 2 hours. The catalyst composition is shown in Table 2.
[0052]
Example 8
[0053] 150 g of boehmite and 3.0 g of guar gum powder were weighed, and then 145 mL of an aqueous solution containing 1.5 g of acetic acid was added. The mixture was extruded into 2.0 mm clover-shaped strips. The wet strips were dried at 110 °C for 12 hours and then calcined at 1200 °C for 5 hours to obtain alumina support Z5. 100 g of the support was weighed, and a catalyst was prepared by weighting the catalyst according to the ratio of 5% Ni + 5% Ag + 0.5% K + 7% S. Nickel nitrate, silver nitrate, and potassium nitrate were weighed and dissolved in water to a volume of 60 mL. The support was impregnated in the solution in equal amounts, dried at 120 °C for 6 hours, calcined at 450 °C for 6 hours, and then reduced for 16 hours at 440 °C, 0.7 MPa, and H2 space velocity of 1300 h⁻¹. Finally, the catalyst was subjected to a H2 atmosphere containing 2 mol% sulfur (dimethyl disulfide) at 360 °C, 0.7 MPa, and a gas space velocity of 750 h⁻¹. -1 Catalyst C8 was obtained by sulfidation treatment for 8 hours under the specified conditions. The composition of the catalyst is shown in Table 2.
[0054]
Comparative Example 1
[0055] Using Z1 as the support, 100g of the support was weighed. Based on the catalyst weight, a catalyst was prepared according to the ratio of 20% Ni + 5% Ag + 1.5% K. Nickel nitrate, silver nitrate, and potassium nitrate were weighed and dissolved in water to a final volume of 85ml. The support was then impregnated in the solution in equal amounts, dried at 110℃ for 6 hours, calcined at 450℃ for 7 hours, and then subjected to a reaction at 450℃, 0.1 MPa, and an H2 space velocity of 1000 h⁻¹. -1 The catalyst CD1, which is free of sulfur, was prepared by reduction under the specified conditions for 15 hours. The composition of the catalyst is shown in Table 3.
[0056] [Comparative Example 2]
[0057] Using Z2 as a support, 100g of support was weighed. Based on the catalyst weight, a catalyst was prepared according to a ratio of 30% Ni + 2.0% Li + 6% S. First, nickel nitrate and lithium nitrate were weighed and dissolved in water to a final volume of 88ml. The support was then impregnated in the solution in equal amounts, dried at 120℃ for 4 hours, calcined at 500℃ for 4 hours, and then subjected to a reaction at 500℃, 0.6MPa, and an H2 space velocity of 500h⁻¹. -1 The sample was reduced for 30 hours under the specified conditions, and then further reduced in an H2 atmosphere containing 2 mol% sulfur (dimethyl disulfide) at 300 °C, 0.6 MPa, and a gas hourly space velocity of 600 h⁻¹. -1 Catalyst CD2 was obtained by sulfidation treatment for 8 hours under the specified conditions. The composition of the catalyst is shown in Table 3.
[0058] [Comparative Example 3]
[0059] Using Z3 as the support, 100g of the support was weighed. Based on the catalyst weight, a catalyst was prepared according to the ratio of 15% Ag + 1.0% Li + 1.0% K + 4% S. Silver nitrate, lithium nitrate, and potassium nitrate were weighed and dissolved in water to a final volume of 75ml. The support was then impregnated in the solution in equal amounts, dried at 130℃ for 7 hours, calcined at 550℃ for 5 hours, and then subjected to a reaction at 480℃, 0.7 MPa, and an H2 space velocity of 1500 h⁻¹. -1 The sample was reduced for 10 hours under the following conditions, and then subjected to a H2 atmosphere containing 2 mol% sulfur (carbon disulfide) at 350°C, 0.7 MPa, and a gas space velocity of 400 h⁻¹. -1 Catalyst CD3 was prepared by sulfidation treatment for 4 hours under the specified conditions. The composition of the catalyst is shown in Table 3.
[0060] [Comparative Example 4]
[0061] Weigh 150 g of boehmite and 3.0 g of guar gum powder, then add 145 ml of an aqueous solution containing 25 g of polyvinyl alcohol solution (mass concentration of 5%), 2.0 g of nitric acid and 1.5 g of acetic acid, and extrude into 2.0 mm clover strips. After drying the wet strips at 110 °C for 12 hours, they are calcined at 950 °C for 4 hours to obtain alumina carrier D1.
[0062] Weigh 100g of support and prepare the catalyst by weight of 20% Ni + 5% Ag + 1.5% K + 5% S. First, weigh out nickel nitrate, silver nitrate, and potassium nitrate, and dissolve them in water to make 85ml of solution. Impregnate the support in the solution in equal volumes, dry at 110℃ for 6 hours, calcine at 450℃ for 7 hours, and then calcine at 450℃, 0.1MPa, and H2 space velocity of 1000h⁻¹. -1 The sample was reduced for 15 hours under the specified conditions, and then further reduced in an H2 atmosphere containing 2 mol% sulfur (hydrogen sulfide) at 320°C, 0.1 MPa, and a gas hourly space velocity of 500 h⁻¹. -1 Under the specified conditions, the catalyst CD4 was prepared by sulfidation treatment for 5 hours. The catalyst composition is shown in Table 3.
[0063] Table 1
[0064]
[0065] Table 2
[0066]
[0067]
[0068] Table 3
[0069]
[0070]
[0071]
Example 9
[0072] This embodiment illustrates the application of the catalysts obtained in Examples 1-8 in the selective hydrogenation of vinylacetylene in C4 fractions. 100 mL of each catalyst from Examples 1-8 of this invention was loaded into a fixed-bed reactor. The reaction was carried out at a hydrogen pressure of 1.5 MPa, a reaction temperature of 40°C, and a fresh oil space velocity of 1.5 h⁻¹. -1 The experiment was conducted by introducing C4 fraction feedstock under a hydrogen / oil volume ratio of 100:1. The C4 fraction feedstock had the following weight percentage composition: 5.0% vinylacetylene, 30% butadiene, and the balance being butene-1. The hydrogenation results are shown in Table 4.
[0073] [Comparative Example 5]
[0074] Take 100 mL of each catalyst from Comparative Examples 1-4. Conduct experiments using the same apparatus, raw materials, and reaction conditions as in Example 9. The hydrogenation results are shown in Table 4.
[0075] Table 4
[0076]
[0077]
[0078]
Example 10
[0079] This embodiment illustrates the experimental results of selective hydrogenation of vinylacetylene in C4 fraction of the present invention using catalyst C1 from Example 1 for 1000 hours. 100 mL of catalyst C1 from Example 1 was used, and the experiment was conducted using the same apparatus, raw materials, and reaction conditions as in Example 9. The hydrogenation results are shown in Table 5.
[0080] Comparative Example 6
[0081] Take 100 mL of catalyst CD4 from Comparative Example 4 and conduct an experiment using the same apparatus, raw materials, and reaction conditions as in Example 9. The hydrogenation results are shown in Table 5.
[0082] Table 5
[0083]
[0084]
Claims
1. A method for selective hydrogenation of vinylacetylene in a C4 fraction, comprising, under effective reaction conditions, a step of contacting the vinylacetylene in the C4 fraction with a catalyst to increase butadiene production, characterized in that, The catalyst comprises the following components by weight percentage: (a) 5.0 to 40.0% metallic nickel or its oxide, based on the content of nickel element therein; (b) 1.0 to 20.0% metallic silver or its oxide, based on the content of silver element therein; (c) 0.1% to 3.0% of at least one element selected from IA of the periodic table or its oxide, based on the content of the IA element therein; (d) 1.0 to 10.0% sulfur or its compounds, wherein the sulfur or its compounds are at least one of hydrogen sulfide, dimethyl disulfide, and carbon disulfide, based on the content of sulfur element therein; (e) Balance of aluminum oxide; The catalyst has a specific surface area of 50-200 m². 2 / g, pore volume of 0.4-0.6cm 3 / g, the effective reaction conditions include: hydrogen pressure 1.0-2.0 MPa, reaction temperature 30-80℃, and fresh oil space velocity 1.0-2.0 h⁻¹. -1 Hydrogen / oil volume ratio 50:1-200:1; The catalyst is prepared by the following method: (1) The pseudoboehmite, guar gum powder, adhesive solvent and water are mixed and shaped, and then dried and calcined in air to obtain the modified alumina carrier; (2) The solution composed of nickel precursor, silver precursor and group IA metal precursor is brought into contact with the above modified alumina support. The support after contact is dried and calcined in air to obtain an oxidized catalyst. (3) Reduced under certain conditions, and then sulfided in a hydrogen atmosphere containing sulfur or its compounds to obtain the catalyst product. In step (1), the drying temperature for preparing the modified alumina carrier is 100-150℃ and the drying time is 10-15h; the calcination temperature is 1000-1200℃ and the calcination time is 4-8h.
2. The method for selective hydrogenation of vinylacetylene according to claim 1, characterized in that, The catalyst, by weight percentage, comprises 10.0-30.0% nickel or its oxide; 3.0-15.0% silver or its oxide; 0.2-2.0% at least one element selected from IA of the periodic table or its oxide; and 2.0-8.0% sulfur or its compound.
3. The method for selective hydrogenation of vinylacetylene according to claim 1 or 2, characterized in that, The element selected from IA of the periodic table is at least one of lithium or potassium.
4. The method for selective hydrogenation of vinylacetylene according to claim 1 or 2, characterized in that, The adhesive solvent is at least one of nitric acid, acetic acid, and polyvinyl alcohol.
5. The method for selective hydrogenation of vinylacetylene according to claim 1 or 2, characterized in that, The nickel precursor mentioned in step (2) is nickel nitrate; the silver precursor is silver nitrate.
6. The method for selective hydrogenation of vinylacetylene according to claim 1 or 2, characterized in that, The drying temperature for preparing the oxidized catalyst in step (2) is 100-150℃ and the drying time is 4-10h; the calcination temperature is 400-600℃ and the calcination time is 4-8h.
7. The method for selective hydrogenation of vinylacetylene according to claim 1 or 2, characterized in that, The reduction conditions described in step (3) are: temperature 400-500℃, pressure 0.1-1.0MPa, and hydrogen space velocity 500-1500h. -1 The restoration time is 10-30 hours.
8. The method for selective hydrogenation of vinylacetylene according to claim 1 or 2, characterized in that, The vulcanization conditions described in step (3) are: temperature 300-400℃, pressure 0.1-1.0MPa, and gas space velocity 400-800h. -1 Vulcanization time: 2-10 hours.
Citation Information
Patent Citations
Acetylene hydrocarbon selective hydrogenation method
CN101434508A
Utilization method of butadiene extraction device residue
CN1590353A
Catalyst and application as well as preparation method thereof
CN103301838A
Improvements in and relating to selective hydrogenation proceses
GB646408A